Bridging the Artificial Intelligence Skills Gap in Learning: An Undergraduate Perspective in Bangladesh - Rajib Chandra Das; Jahid Hasan Asik; Jahid Hasan; Tasfia Jahan Sifa (CV Projurnal Mitra Publikasi, 2025)
The rapid integration of Artificial Intelligence (AI) into higher education is reshaping teaching, learning, and research worldwide. In Bangladesh, university students are increasingly engaging with AI tools for academic purposes. This research article explores the impact of AI on higher education by examining its effects on the learning process from the perspective of undergraduate students. The study followed a quantitative, descriptive-exploratory research design, using survey questionnaires for primary data collection. The research was conducted using Google Forms among students from six universities from diverse disciplines. Survey data obtained from over 200 students across two private and two public universities. Findings reveal that a majority of respondents use AI tools frequently for academic purposes, writing assistance, and conceptual understanding. The perceived benefits include enhanced learning efficiency, improved academic skills, and access to personalized learning resources. At the same time, students articulated critical concerns regarding data privacy, ethical misuse, diminished creativity, and unequal access to advanced AI technologies. These insights highlight both the opportunities and risks of AI adoption in Bangladesh’s higher education sector. The study concludes with recommendations for integrating AI literacy into curricula, developing institutional guidelines, and inclusive use of AI.